Manejo cultural do maracujazeiro-amarelo em ciclo anual visando à convivência com o vírus do endurecimento dos frutos: Um estudo de caso - Sampaio, Aloísio Costa [UNESP]; Scudeller, Nilton; Fumis, Terezinha De Fátima [UNESP]; De Almeida, Aparecida Marques; Pinotti, Raquel Nakasato; Garcia, Maria José De Marchi; Pallamin, Maria Lúcia [UNESP] (FapUNIFESP (SciELO), 2008)
This case study aimed to analyze the quality of fruits and productivity in t/ha of the yellow passion fruit in two annual cycles, respectively on October 4th, 2004 (1st planting) and August 20th, 2005 (2nd planting). In the 1st planting it was eradicated on the July 13th, 2005, in function of the orchard presenting the totality of the plants with typical symptoms of PWV in fruits and leaves. The seedlings of the selection Afruvec were formed in plastic tubes inside greenhouse with anti-aphid screen. The orchard in both productive cycles was irrigated by leaking being adopted a density of 1.600 plants per hectare. In both plantings there was no necessity of elimination of plants, since the beginning of the symptoms of PWV happened when the plants were in the middle of the flowering. In the 1st planting the symptoms began on the January 26th, 2005 and in the 2nd planting, on the January 4 th, 2006. For the results, it can be concluded that the regionally handling adopted with annual cycle planting, allowed an amplification of the crop period, due to the planting anticipation of the 2nd year, productivity of 16,94 kg/plant and 18,39 kg/plant, in the 1st and 2nd year, respectively; increase the profitability in the crop of 2006 in function of the best production and quotation of the fruits in natura and for industry; and mainly, a reduction of the potential of regional inoculum, seeking a sustainable production.
Handling of the of yellow passion fruit plant in annual cycle aiming the coexistence with the PWV (passion fruit woodiness virus): A case study
Keywords: Passiflora edulis Sims f. flavicarpa Deg.; Sustainability; Viruses